St. Lucia : Technical Assistance Report-Report on Supply and Use Tables Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
A technical assistance (TA) mission was undertaken by the Real Sector Statistics Advisor in the Caribbean Regional Technical Assistance Centre (CARTAC) to St. Lucia during September 17-28, 2018, to provide advice to the Central Statistics Office (CSO) on compiling supply and use tables (SUT) for 2016. The 2006 base year for the GDP estimates is outdated and does not reflect the current structure of the economy. In addition, there is scope to improve the input data and methodology used in producing the GDP estimates and to implement the relevant System of National Accounts 2008 (2008 SNA) recommendations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet